Impact of increased aspartate aminotransferase to alanine aminotransferase (De Ritis) ratio in prognosis of testicular cancer - Gorgel, Sacit Nuri (Investig Clin Urol, 2019)
PURPOSE: Imaging studies can show metastasis in testicular cancer (TCa); however, a test for risk of metastasis in TCa has not been described. The ratio of aspartate aminotransferase to alanine aminotransferase, also called the De Ritis ratio (DRR), is used for many other malignancies. We aimed to evaluate the association between preoperatively assessed DRR and prognosis in patients with TCa. MATERIALS AND METHODS: One hundred twenty-eight patients with TCa were enrolled in a retrospective study between March 2007 and January 2017. Clinical, biochemical, and pathological data were recorded. Univariate and multivariate logistic regression analyses were used. The prognostic value of DRR and the threshold value were assessed by use of receiver operating characteristic curves. Significance was defined as p<0.05. RESULTS: Mean follow-up was 37±9.7 months. There were 45 and 73 TCa patients with and without lymph node metastasis, respectively. Lung metastases and other solid organ metastases occurred in 14 and 4 patients, respectively. The optimal DRR threshold was 1.30 for both retroperitoneal lymph node involvement and metastasis. DRR was determined as an independent prognostic factor for retroperitoneal lymph node involvement and organ metastasis in univariate and multivariate analyses (p<0.001, p=0.006 and p=0.002, p=0.047, respectively). CONCLUSIONS: A preoperative DRR greater than 1.30 may be an independent risk factor for retroperitoneal lymph node involvement and organ metastases in patients with TCa.